2022
DOI: 10.1021/acsaelm.2c01123
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Porous PDMS-Based Piezoresistive Sensor Prepared by a Modified Microwave Irradiation Process

Abstract: The flexible pressure sensor based on a porous structure has excellent sensing performance. It is critical to develop a large-scale and lowcost manufacturing method for realizing high-performance flexible sensors with porous structures. Herein, a porous polydimethylsiloxane (PDMS) was prepared by a modified microwave irradiation process, and an ultrahigh sensitive flexible piezoresistive sensor with wide sensing range was obtained by coating carbon nanotubes (CNTs)/graphene on the porous PDMS surface. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Upon the release of pressure, the porous PDMS returns to its original state due to its elasticity, leading to a reduction in the conductive pathways between the pore walls, and hence the restoration of the sensor resistance to its initial value. 190 According to Euler's critical load, the critical force at which buckling occurs is inversely proportional to the length of the thin column between pores. 192 Given that the column of larger pores is longer, buckling would occur at a relatively lower pressure.…”
Section: Preparation Methods and Mechanisms Of Porous Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon the release of pressure, the porous PDMS returns to its original state due to its elasticity, leading to a reduction in the conductive pathways between the pore walls, and hence the restoration of the sensor resistance to its initial value. 190 According to Euler's critical load, the critical force at which buckling occurs is inversely proportional to the length of the thin column between pores. 192 Given that the column of larger pores is longer, buckling would occur at a relatively lower pressure.…”
Section: Preparation Methods and Mechanisms Of Porous Microstructuresmentioning
confidence: 99%
“…Upon the release of pressure, the porous PDMS returns to its original state due to its elasticity, leading to a reduction in the conductive pathways between the pore walls, and hence the restoration of the sensor resistance to its initial value. 190…”
Section: Porous Microstructure Flexible Pressure Sensorsmentioning
confidence: 99%
“…This is mainly because the approaches employed to create surface microstructures are different from those of porous structures. Specifically, the fabrication of microstructures on flexible substrates’ surfaces involves laser ablation, templates, and lithography, while the creation of porous structures of flexible substrates commonly employs the sacrificial template method, chemical foaming method, microwave heating method, and directional freezing. , Therefore, the hybrid structures composed of porous structures and surface microstructures are achieved by multistep processes, which makes the implementation of the sensor time-consuming and difficult. Thus, it is necessary to develop a new, simple, cost-effective, one-step approach to prepare hybrid structures for flexible sensors, but related studies have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible piezoresistive sensors [1][2][3][4] have been widely reported recently because of their promising application in flexible electronics [5,6], motion detection [7,8], and health monitoring [1]. Flexible piezoresistive sensors possess a wide operating range, excellent sensitivity, quick response time, and exceptional repeatability.…”
Section: Introductionmentioning
confidence: 99%